2013
DOI: 10.2337/db12-0207
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Immunogenetics, and Clinical Characteristics of Latent Autoimmune Diabetes in China (LADA China Study)

Abstract: Adult non–insulin requiring diabetes includes latent autoimmune diabetes of adults (LADA), distinguished from type 2 diabetes by the presence of islet autoantibodies. LADA China determined the characteristics of Chinese LADA. This nationwide, multicenter, clinic-based cross-sectional study was conducted in 46 university-affiliated hospitals in 25 Chinese cities. All 4,880 ketosis-free diabetic patients (<1 year postdiagnosis, without insulin therapy for >6 months, aged ≥30 years) had GAD antibody (GADA) and HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
298
3
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 225 publications
(337 citation statements)
references
References 30 publications
30
298
3
3
Order By: Relevance
“…LADA was defined according to the Immunology of Diabetes Society 2004 definition, based on the diagnosis of diabetes at age $30 years old, independence of insulin therapy for at least 6 months, and GADA positivity (10). GADA levels $180 units/mL were defined as "high GADA level," whereas those between 18 and 180 units/mL were defined as "low GADA level" (16). The inclusion criteria were 1) diagnosis of diabetes (World Health Organization [WHO] 1999 criteria) at age $30 years, 2) duration of diabetes ,5 years, and 3) patients with residual islet function (fasting C-peptide…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…LADA was defined according to the Immunology of Diabetes Society 2004 definition, based on the diagnosis of diabetes at age $30 years old, independence of insulin therapy for at least 6 months, and GADA positivity (10). GADA levels $180 units/mL were defined as "high GADA level," whereas those between 18 and 180 units/mL were defined as "low GADA level" (16). The inclusion criteria were 1) diagnosis of diabetes (World Health Organization [WHO] 1999 criteria) at age $30 years, 2) duration of diabetes ,5 years, and 3) patients with residual islet function (fasting C-peptide…”
Section: Subjectsmentioning
confidence: 99%
“…HLA-DQA1 and -DQB1 genotypes were defined by DNA analysis using PCR to amplify exon 2 of both DQA1 and DQB1 genes, followed by standard DNA sequencing-based typing (21). The definition of HLA protective haplotypes and HLA susceptibility haplotypes was according to that in LADA China Study reported by Zhou et al (16).…”
Section: Hla Genotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the autoantibody assays were often negative in Asian T1DM patients. It might due to the unsensitive or unspecific assays, or testing far from diagnosis as antibody titers diminish, yet-to-beidentified auto-antigens, or foremost heterogeneity of islet autoantibodies in Chinese population (Lu et al, 2012;Wang et al, 2007;Zhou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%